Self-Awareness and Bystander Response among University Students: Kesadaran Diri dan Respons Penonton di Kalangan Mahasiswa Universitas - Pagita, Ellyta Dirgadini; Mariyati, Lely (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The bystander effect describes individuals’ reluctance to intervene in social emergencies. Specific Background: In university settings, self-awareness may play a crucial role in determining whether students act or remain passive. Gap: Previous studies have largely examined bystander behavior without considering internal self-regulation factors. Aim: This study aims to analyze the relationship between self-awareness and the bystander effect among university students. Results: The findings indicate a significant negative correlation, meaning that higher self-awareness levels correspond to lower bystander tendencies. Novelty: This study highlights the importance of self-awareness as a psychological factor influencing prosocial actions in educational contexts. Implications: The results can inform character education and social responsibility programs in higher education to reduce social apathy among students. Highlights:• The study connects self-awareness to bystander behavior• Findings support the role of self-regulation in prosocial acts• Provides evidence from university students in Indonesia Keywords: Bystander Effect, Self-Awareness, Prosocial Behavior, Higher Education, Psychology